2020
DOI: 10.1021/acs.chemmater.0c01990
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Mediated Synthesis of Amorphous Li3PS4/Polyethylene Oxide Composite Solid Electrolytes with High Li+ Conductivity

Abstract: Solvent-mediated routes have emerged as an effective, scalable, and low-temperature method to fabricate sulfide-based solid-state electrolytes. However, tuning the synthesis conditions to optimize the electrolyte’s morphology, structure, and electrochemical properties is still underexplored. Here, we report a new class of composite solid electrolytes (SEs) containing amorphous Li3PS4 synthesized in situ with a poly­(ethylene oxide) (PEO) binder using a one-pot, solvent-mediated route. The solvent and thermal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Nanda et al and Tatsumisago et al have previously used XRD to conrm amorphous LPS formation where LPS is reported to exhibit one broad peak around 19 (observed in Sample 2). 43,46 The second peak at 30 in Sample 2 corresponds to the Kapton lm background (Fig. S2 †).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nanda et al and Tatsumisago et al have previously used XRD to conrm amorphous LPS formation where LPS is reported to exhibit one broad peak around 19 (observed in Sample 2). 43,46 The second peak at 30 in Sample 2 corresponds to the Kapton lm background (Fig. S2 †).…”
Section: Resultsmentioning
confidence: 99%
“…45,52,53 The visual color differences indicate likely unreacted precursors in Sample 1, and X-ray diffraction (XRD) was used to determine the differences. [38][39][40][41]43 Because Li 2 S crystallizes in the cubic space group Fm 3 m, weak reections within the amorphous LPS spectra corresponding to unreacted Li 2 S were expected. 43 However, as Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations